2012
DOI: 10.1074/jbc.m112.381517
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II and MARCKS

Abstract: Background:The role of the actin-binding protein MARCKS in angiotensin-II signaling is unknown. Results: Biochemical and cell imaging approaches establish that angiotensin-II promotes Rac1-and H 2 O 2 -dependent MARCKS phosphorylation and cytoskeleton rearrangement. Conclusion: MARCKS plays a critical role in angiotensin-II signaling. Significance: Angiotensin-II is implicated in vascular physiology and pathophysiology; these studies identify MARCKS as a key determinant of angiotensin-II-modulated responses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…As previously shown (Jin et al 2012;Kalwa et al 2012Kalwa et al , 2014Kalwa and Michel 2011), MARCKS phosphorylation in endothelial cells is reduced by the tyrosine kinase inhibitor bosutinib. Bosutinib also inhibited MARCKS phosphorylation in HT-29 cells (Fig.…”
Section: Role Of Marcks Phosphorylation For Regulation Of Abcb1 Functionsupporting
confidence: 64%
See 2 more Smart Citations
“…As previously shown (Jin et al 2012;Kalwa et al 2012Kalwa et al , 2014Kalwa and Michel 2011), MARCKS phosphorylation in endothelial cells is reduced by the tyrosine kinase inhibitor bosutinib. Bosutinib also inhibited MARCKS phosphorylation in HT-29 cells (Fig.…”
Section: Role Of Marcks Phosphorylation For Regulation Of Abcb1 Functionsupporting
confidence: 64%
“…Monitoring of fluorescence resonance energy transfer (FRET) biosensors was performed using methods described in detail previously (Aoki et al 2013;Kalwa et al 2012Kalwa et al , 2014Kalwa and Michel 2011). In brief, HT-29 cells were transfected with plasmids encoding FRET biosensors as indicated.…”
Section: Fret Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…MARCKS increases cell motility through the protein kinase B pathway in fibroblasts21 and glial cells 22. Motility is also potentiated in macrophages,23 neutrophils,24 skeletal myoblasts,25 and endothelial cells26 through direct binding of MARCKS to actin. However, the mechanism through which MARCKS regulates VSMC motility is as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MeHg is known to induce reactive oxygen species (ROS) production, including hydrogen peroxide (H 2 O 2 ). Since the distinct role of MARCKS accompanying its phosphorylation in H 2 O 2 -mediated signaling pathway in bovine aortic endothelial cells has been reported [16, 18], MARCKS is possibly phosphorylated through mechanisms associated with MeHg-induced H 2 O 2 production in EA.hy926 cells. Although we previously reported that, in neuroblastoma cells, the MARCKS phosphorylation by MeHg exposure was mediated by protein kinase C activation and occurred in a Ca 2+ -dependent manner, the phosphorylation mechanisms in EA.hy926 cells are still not clear and remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%